A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan - Nakajima, Jun; Kamite, Yuuki (Zootaxa, 2020)
A new species, Urumaelmis flammea Nakajima and Kamite, sp. nov., is described from Kyushu, Japan. This is the second species of the genus Urumaelmis Satô, 1963. The new species differs from the previously known species in the body size, the elytral carinae, and the shape of the aedeagus.